Uses and abuses of the OECD’s Employment Protection Legislation index in research and EU policy making - Myant, Martin; Brandhuber, Laura (Brussels, 2016)
"This paper provides a critical assessment of the OECD's Employment Protection Legislation (EPL). This indicator is designed to measure and compare employment protection legislation across countries and has dominated much of recent labour market policy making in the EU.